2010
DOI: 10.2174/1874325001004010039
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Cervical Spondyloarthropathy in Hemodialysis Patients

Abstract: Dialysis-related spondyloarthropathy is a rare cause of spinal deformity and cervical myelopathy. Optimal management of cervical spine spondyloarthropathy often requires circumferential reconstructive surgery, because affected patients typically have both the anterior column and the facet joints compromised. The occasional presence of noncontiguous or "skip lesions" adds an additional level of complexity to surgical management, because decompression and fusion in an isolated segment of neural compression can w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There have been many reports of hardware failure and the need for revision surgery after anterior corpectomy or discectomy and fusion due to fragility of the bones in dialysis patients. [45][46][47] In addition, invasive surgical procedures might increase the risk of postoperative complications and mortality in patients on longterm hemodialysis who have multiple comorbidities and poor health condition. Chikuda et al 48 reported that dialysis-depen-dent patients had a 10-fold higher risk of in-hospital mortality.…”
Section: Revision Surgery For Destructive Spondyloarthropathy Relatedmentioning
confidence: 99%
“…There have been many reports of hardware failure and the need for revision surgery after anterior corpectomy or discectomy and fusion due to fragility of the bones in dialysis patients. [45][46][47] In addition, invasive surgical procedures might increase the risk of postoperative complications and mortality in patients on longterm hemodialysis who have multiple comorbidities and poor health condition. Chikuda et al 48 reported that dialysis-depen-dent patients had a 10-fold higher risk of in-hospital mortality.…”
Section: Revision Surgery For Destructive Spondyloarthropathy Relatedmentioning
confidence: 99%
“…We can regroup rare neurologic complications which can cause narrowing of the cervical canal such ankylosing spondylitis, gouty tophi from the posterior joints and vertebral ankylosing hyperostosis (Forestier's disease) or Paget's disease. Myelopathies have been observed in patients on long-term dialysis due to epidural calcification (85). ++++…”
Section: Other Etiologiesmentioning
confidence: 99%
“…The cervical spine is the most common site for hemodialysis-related lesions, and cervical DSA severely restricts the activities of daily living for hemodialysis patients. Several reports have described the surgical outcome and long-term follow-up results for hemodialysis patients with lower cervical lesions [ 2 3 4 5 6 ]. Other reports have described upper cervical lesions in patients receiving long-term hemodialysis [ 7 8 9 10 11 12 13 14 15 16 ].…”
Section: Introductionmentioning
confidence: 99%